Safety and efficacy of continuous subcutaneous foslevodopa-foscarbidopa in patients with advanced Parkinson's disease: a randomised, double-blind, active-controlled, phase 3 trial. Issue 12 (December 2022) - Soileau, Michael J; Aldred, Jason; Budur, Kumar; Fisseha, Nahome; Fung, Victor SC; Jeong, Anna; Kimber, Thomas E; Klos, Kevin; Litvan, Irene; O'Neill, Daniel; Robieson, Weining Z; Spindler, Meredith A; et al.
Summary: Background: Levodopa is the most effective symptomatic therapy for Parkinson's disease, but patients with advanced Parkinson's disease develop motor fluctuations with chronic oral levodopa therapy. Foslevodopa-foscarbidopa is a soluble formulation of levodopa and carbidopa prodrugs that is delivered as a 24-h/day continuous subcutaneous infusion, and we aimed to assess the safety and efficacy of this formulation in patients with advanced Parkinson's disease. Methods: A 12-week randomised, double-blind, double-dummy, active-controlled study was done at 65 academic and community study centres in the USA and Australia. Patients with levodopa-responsive advanced Parkinson's disease inadequately controlled on current therapy, including at least 2·5 h of average daily off time, were randomly assigned (1:1) to continuous subcutaneous infusion of foslevodopa-foscarbidopa plus oral placebo or to oral immediate-release levodopa-carbidopa plus continuous subcutaneous infusion of placebo solution. Randomisation was stratified by site by means of a permutated-block schedule with a block size of two. The participants, treating investigators, study site personnel, and sponsor were masked to treatment group allocation. The primary and first key secondary endpoint in the hierarchical testing strategy were change from baseline to week 12 in on time without troublesome dyskinesia and off time, respectively; both endpoints were evaluated by an intention-to-treat analysis applying a mixed model for repeated measures analysis. Safety and tolerability were assessed throughout the study. The study is completed and is listed on ClinicalTrials.gov, NCT04380142 . Findings: Between Oct 19, 2020, and Sept 29, 2021, of 270 participants screened and 174 enrolled, 141 were randomly assigned and received continuous subcutaneous infusion of foslevodopa-foscarbidopa plus oral placebo capsules (n=74) or oral encapsulated immediate-release levodopa-carbidopa plus continuous subcutaneous infusion of placebo solution (n=67). Compared with levodopa-carbidopa, foslevodopa-foscarbidopa showed a significantly greater increase in on time without troublesome dyskinesia (model-based mean [SE] 2·72 [0·52] vs 0·97 [0·50] h; difference 1·75 h, 95% CI 0·46 to 3·05; p=0·0083) and a significantly greater reduction in off time (−2·75 [0·50] vs −0·96 [0·49] h; difference −1·79 h, −3·03 to −0·54; p=0·0054). Hierarchical testing ended after the first secondary endpoint. Adverse events were reported in 63 (85%) of 74 patients in the foslevodopa-foscarbidopa group versus 42 (63%) of 67 in the levodopa-carbidopa group, and incidences of serious adverse events were similar between the groups (six [8%] of 74 vs four [6%] of 67, respectively). The most frequent adverse events in the foslevodopa-foscarbidopa group were infusion site adverse events (erythema 20 [27%]), pain 19 [26%]), cellulitis (14 [19%]), and oedema (nine [12%]), most of which were non-serious and mild–moderate in severity. The only system organ class that had more than one serious adverse event in the foslevodopa-foscarbidopa group was infections and infestations (catheter site cellulitis [one [1%]] and infusion site cellulitis [one [1%]). Adverse events led to premature discontinuation of study drug in 16 (22%) of 74 participants in the foslevodopa-foscarbidopa group versus one (1%) of 67 participants in the oral levodopa-carbidopa group. Interpretation: Foslevodopa-foscarbidopa improved motor fluctuations, with benefits in both on time without troublesome dyskinesia and off time. Foslevodopa-foscarbidopa has a favourable benefit-risk profile and represents a potential non-surgical alternative for patients with advanced Parkinson's disease. Funding: AbbVie.